Identification of Tempeh Wastewater Quality and Analysis of Producer Behavior towards Waste Management in Plaju Ulu - Destri, Erin; Rejo, Amin; Hanum, Laila (Sriwijaya Journal of Environment, 2024)
The development of the household-scale tempeh industry in Plaju Ulu has the opportunity to disrupt the balance of environmental ecosystem if it is not balanced with treatment. Efforts to identify the quality of wastewater and the behavior of tempeh producers need to be carried out in order to immediately prevent the impact caused by waste and become basis for determining the right treatment method. This study uses mix methods approach. Quantitative methods were used  to the identification of BOD, COD, TSS, and pH. Qualitative method was used to find out the behavior of producers. The results showed that soaking stage produced a pH level of 3,830; TSS 22,350 mg/l; COD 27,214.100 mg/l, and BOD 224 mg/l.  Washing stage produce a pH of 4,530; TSS 787,500 mg/l; COD 1187,200 mg/l, and BOD of 7 mg/l.  Boiling stage produces pH 5.3; TSS 1165 mg/l; COD 45,332.8 mg/l, and BOD 295 mg/l. Separation stage of soybean produce TSS 117 mg/l; COD 676,320; BOD 400 mg/l and pH level 6.930. Watering stage produce BOD level of 160 mg/l. Tempeh producers have been aware about importance of waste management process to maintain environmental balance, but as many as 81% of producers still dispose